VD_FINDINFO HC / 2014 / 72 vom 12. März 2014 - VD Tribunal cantonal (2014)
ARCHITECTE, CONTRAT D'ARCHITECTE, DÉFAUT DE LA CHOSE, DOMMAGE, CONTRAT, DILIGENCE, PLUS-VALUE, DEVIS | 321a CO, 398 CO, 97 CO, 317 CPC (CH)